Analisis Dampak Menurunnya Daya Beli Di Lingkungan Masyarakat Indonesia Akibat Inflasi - Elma Nurkhanifah Nurkhanifah (Sahmiyya, 2023)
The purpose of this research is to find out that people's purchasing power has decreased due to one of the factors, namely inflation. This research method uses a literature review approach sourced from journals related to the decline in purchasing power due to inflation. The results of this research literature review conclude that people's purchasing power began to decline dramatically during the co-19 pandemic. One of the factors causing the decline in people's purchasing power is due to the increasing inflation. Especially when the covid-19 pandemic greatly affects the inflation rate. The more inflation increases, the more the purchasing power of people in Indonesia will decrease. The occurrence of inflation affects people's purchasing power which is now declining. This is because the Indonesian people themselves have a tendency towards purchasing power that is so low or stagnant. Inflation is one of the important economic indicators, its growth rate is always sought to be low and stable so as not to cause macroeconomic diseases that will have an impact on instability in the economy. An increase in inflation without an increase in people's income in general will result in a decrease in purchasing power. If this condition occurs continuously (long term) then a negative chain reaction will reduce the economy of a country. This can happen because declining purchasing power in the long term will result in a decline in company performance so that it can have an impact on employee rationalization. The more people whose purchasing power decreases, it can have a negative impact on the country's economy.